KAJIAN BIOMASA TEGAKAN ATAS PERMUKAAN (ABOVEGROUND BIOMASS) DAN CADANGAN KARBON DI BEBERAPA TAMAN KOTA PONTIANAK - Maryadi, Andi; Rafdinal, Rafdinal; Linda, Riza (Jurnal Protobiont, 2019)
Pontianak as the a city the of West Kalimantan, of course, encountered the descrease of land from year to year. This issue leads to the increase of carbon emission in the air. The aim of this research is to find out howmuch biomass and reserved carbon on the surface of gardens in the Pontianak city. This study was conducted from March to June 2017. This used non-destructive methods and alometric equations, data collection was gathered through census on each stand up by measuring DBH â‰¥ 5 cm. The results of this study shows that biomass above the oil surface at five gardens in Pontianak city was around 36,85-473,42 ton/Ha and reserves carbon was around 18,42-236,71 ton C/Ha. The highest reserve carbon was on street of Jalan Ahmad Yani 1 with the value of reserved carbon was around 236.71 ton C/Ha and the lowest reserved carbon was at the garden of Tugu Khatulistiwa, that was 18.42 ton C/Ha.